Bacterial meningoencephalitis in a free Chimango Caracara (Milvago chimango temucoensis) - Seguel, Mauricio; Moroni, Manuel; Gomez, Marcelo; Hernández, Carlos; Paredes, Enrique (Brazilian Journal of Veterinary Pathology, 2012)
A subadult male Chimango Caracara (Milvago chimango temucoensis) was found in an agricultural beef cattle field of Southern Chile. The bird was non-responsive to visual or auditory stimulation, and unable to fly. Clinical examination showed moderate body condition, partial blindness and a left wing fracture. The bird was euthanized and a complete necropsy was performed. The most important macroscopic findings were a complete left radius fracture, a subcutaneous hematoma over the occipital bone region and the complete loss of structure of the left pallium and striatum of the telencephalon. Necrotic areas of greenish discoloration in the caudal telencephalon were observed. Histologically, the brain had wide areas of liquefactive necrosis surrounded by abundant inflammatory infiltrate. Escherichia coli was isolated from the affected areas of the brain. Although bacterial encephalitis is uncommon among free ranging birds, it should be considered as a candidate diagnosis in wild birds with neurological signs.